Individualized Treatment from Theory to Practice: The Private Case of Adding LH during GnRH Antagonist-based Stimulation Protocol - Shahar Kol (SAGE Publishing, 2014)
The study evaluated the proportion of patients whose pituitary glands respond with a sharp decrease in luteinizing hormone (LH) levels when exposed to a conventional dose of 0.25 mg gonadotropin releasing hormone (GnRH) antagonist in a prospective, single-center, non-randomized, proof-of-concept study. Fifty women eligible for in vitro fertilization (IVF) received recFSH (Gonal-F) from day 2 or 3 of menstrual period. Basal estradiol, progesterone, and LH were measured on the same day and 4-5 days later--immediately before GnRH antagonist 0.25 mg administration, and 24 hours after its administration. Responders were defined as "normal" if 24 hours after the first GnRH antagonist injection, LH level was ≥50% of the pre-injection level and as "over-suppressed" if it was <50% of the pre-injection level. Twelve patients (26% of the total) were "over-suppressed" with a mean LH level of 37% of the level 24 hours earlier. These patients also demonstrated a significant decrease in estradiol rise during the first 24 hours after initial antagonist administration. This effect was reversed for the rest of the stimulation period during which recLH (Luveris, 150 IU/day) was added to the "over-suppressed." If proven advantageous in terms of pregnancy rate, this approach to individualized treatment would be easy to implement. Trial registration: ClinicalTrials.gov Identifier: NCT01936077.